2023
DOI: 10.1021/acs.est.2c08467
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Direct Electron Transfer Mediated Contaminant Degradation by Fe(IV) Using a Carbon Black-Supported Fe(III)-TAML Suspension Electrode System

Abstract: Iron complexes of tetra-amido macrocyclic ligands (Fe-TAML) are recognized to be effective catalysts for the degradation of a wide range of organic contaminants in homogeneous conditions with the high valent Fe(IV) and Fe(V) species generated on activation of the Fe-TAML complex by hydrogen peroxide (H2O2) recognized to be powerful oxidants. Electrochemical activation of Fe-TAML would appear an attractive alternative to H2O2 activation, especially if the Fe-TAML complex could be attached to the anode, as this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…This result suggests that structural Fe­(II), rather than aqueous Fe 2+ dominated the formation of PMSO 2 [i.e., Fe­(IV)]. Many previous studies have demonstrated the formation of aqueous Fe­(IV) during the oxidation of Fe 2+ in advanced oxidation processes. Our results extended the generation of Fe­(IV) from homogeneous Fe 2+ systems to structural Fe­(II) associated with clay minerals.…”
Section: Resultssupporting
confidence: 67%
“…This result suggests that structural Fe­(II), rather than aqueous Fe 2+ dominated the formation of PMSO 2 [i.e., Fe­(IV)]. Many previous studies have demonstrated the formation of aqueous Fe­(IV) during the oxidation of Fe 2+ in advanced oxidation processes. Our results extended the generation of Fe­(IV) from homogeneous Fe 2+ systems to structural Fe­(II) associated with clay minerals.…”
Section: Resultssupporting
confidence: 67%
“…The electronic structures of transition metals (TMs) are intimately connected to the conguration of atomic orbital hybridization. [14][15][16] Novel methodologies to regulate the d orbitals of TMs have recently been exploited. [17][18][19] For example, Liu et al designed asymmetrically coordinated Fe-N 3 C 2 to promote Fe (3d)-S (2p) orbital hybridization, engendering a robust chemical affinity for lithium polysuldes.…”
Section: Introductionmentioning
confidence: 99%
“…A conventional Fenton reaction is mainly based on the generation of free radicals for the degradation of organic pollutants. , However, treatment of practical organic wastewater with free radicals could face a range of challenges, such as natural matrix in water, inorganic ions and even the pH of solution, , which would greatly inhibit the degradation efficiency of organic pollutants. Recently, high-valent metal species, such as high-valent iron (Fe(IV) and Fe(V)), cobalt (Co(IV)), and copper (Cu(III)) , generated in peroxide activated by metal catalysts have been proved to show excellent oxidation ability toward organic pollutants compared to radicals. At the same time, they also had the advantage of higher resistance to environmental interference and even exhibited excellent removal properties on trace pollutants. …”
Section: Introductionmentioning
confidence: 99%